Infrared broadband source from 1000nm to 1700nm, based on an Erbium, Neodymium and Bismuth doped double-clad fiber - Pilz, S.; Etissa, D.; Barbosa, C.; Romano, V. (ALT Proceedings, 2026)
A Nd3+, Er3+ and Bi3+ doped double-clad fiber (core diameter of 25.5μm, cladding diameter of 125μm) with a broad infrared emission has been fabricated based on technique of dry granulated oxides and investigated. Upon the excitation with a 800nm cw pump source all of the three dopant materials showed fluorescence in the infrared region of interest (1000-1700nm). The observed emitted fluorescence power was measured to be 659μW. Changing the pump wavelength to 976nm led to a fluorescence of only Er3+ and Bi3+ and a broadening of the Bi3+ emission peak. The maximal measured fluorescence output power was 1.42mW, when pumped at 976nm.